Bacteriological, serological, and histopathological study of post-weaning piglets experimentally infected with Salmonella Typhimurium = Estudio bacteriológico, serológico e histopatológico de lechones destetados infectados experimentalmente con Salmonella Typhimurium - Joaquim, Patricia Estefania; Balbiani, Facundo; Delgado, Fernando Oscar; Redondo, Leandro Martin; Cappuccio, Javier Alejandro; Chacana, Pablo (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2023)
In the last decades, infections by several serovars of Salmonella have become relevant worldwide, not only due to their impact on veterinary health and animal production, but also because they may serve as a source of infection for the human population. Pigs can be infected by several Salmonella serovars, being S. Typhimurium one of the most frequently isolated worldwide. In this context, the evaluation of strategies to control Salmonella in farms demands the understanding of the pathogenesis of the microorganism. Thus, the objective of this work was to carry out an experimental infection in 50-day-old pigs using a field strain of S. Typhimurium to evaluate the excretion of the microorganism, organs colonization and the development of histological injuries over the 13-day trial period. Disease was successfully reproduced in eight animals, and two clinical patterns were identified. In four animals, a primarily enteric pattern was observed, where the infection was limited to the gastrointestinal tract, while in another four pigs, enteric and systemic infection with variable fecal excretion and invasion of internal organs was observed. These two infectious patterns were accompanied by changes in fecal consistency and reduced daily weight gain or weight loss in the animals. The observation of two different infectious patterns highlights the need to consider the complexity of the pathogenicity of Salmonella Typhimurium infection in pigs.